2020
DOI: 10.31235/osf.io/j2nqb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of COVID-19 on A level students in England

Abstract: The global outbreak of the COVID-19 virus created new and challenging circumstances for schools, colleges and universities. In England the closure of schools and cancellation of examinations led to concerns about how pupils would be awarded A Level exam grades. These exam results have a significant impact on outcomes for pupils leaving school including access to the employment market, apprenticeships and university places. This report represents an early analysis of research exploring the impact school closure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…These lead to enhanced employability outcomes and the ability for graduates to navigate their way in a volatile and rapidly evolving labour market. Moreover, we believe that authentic assessment can address the damage imposed by suggested grade inflation (Bachan, 2016;Stoebe, 2017), which is likely to have been exacerbated due to the impacts of the COVID-19 pandemic (Bhopal & Myers, 2020). Employers can thus gain a tangible benefit from participation and support in the authentic assessment process by helping to shape graduates to meet the current and future needs of the industry (Hinchliffe & Jolly, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These lead to enhanced employability outcomes and the ability for graduates to navigate their way in a volatile and rapidly evolving labour market. Moreover, we believe that authentic assessment can address the damage imposed by suggested grade inflation (Bachan, 2016;Stoebe, 2017), which is likely to have been exacerbated due to the impacts of the COVID-19 pandemic (Bhopal & Myers, 2020). Employers can thus gain a tangible benefit from participation and support in the authentic assessment process by helping to shape graduates to meet the current and future needs of the industry (Hinchliffe & Jolly, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…depression: 32% worse vs. 22% better; anxiety: 27% worse vs. 21% better; wellbeing: 30% worse vs. 25% better). These findings may relate to separate research that also reported mixed findings, with 21% of young people in England stating they were happy that exams were cancelled and 46% stating they would have preferred to sit their exams [ 54 ]. The negative impact of exam cancellations however was particularly noted by adolescents who were experiencing clinically significant symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Following the official announcement of school closures and the cancellation of exams, we conducted a survey questionnaire with a total of 583 A Level students between April and August 2020 (Bhopal and Myers, 2020). Participants were recruited via social media platforms such as Twitter, Facebook and message boards such as Mumsnet and The Student Room.…”
Section: Methodsmentioning
confidence: 99%